Synthesis of 5-Fluoroaminobenzothiazoles - Sharma, Pooja; Singh, Gurdial; Bhongade, Bhoomendra A.; Noolvi, Malleshappa N.; Gadad, Andanappa K. (SynOpen, 2020)
A series of 5-fluoro-2-(N-substituted)aminobenzothiazoles were synthesized by intramolecular cyclisation of the corresponding thioureas, which were prepared by treatment of 4-substituted 3-fluoroanilines with appropriate isothiocyanates.
Keywords: synthetic methods; 2-aminobenzothiazoles; isothiocyanates; chiral; fluoro; heterocyclic